Assembly and comparative genome analysis of four mitochondrial genomes from Saccharum complex species - Li, Sicheng; Yang, Cuifang; Wang, Zhen; Xu, Chaohua; Zhang, Gemin; Huang, Yuxin; Zhang, Baoqing; Zhou, Shan; Gao, Yijing; Zong, Wenyi; Duan, Weixing; Yang, Xiping (Frontiers in Plant Science, 2024)
Saccharum complex includes genera Saccharum, Miscanthus, Erianthus, Narenga, and Tripidium. Since the Saccharum complex/Saccharinae constitutes the gene pool used by sugarcane breeders to introduce useful traits into sugarcane, studying the genomic characterization of the Saccharum complex has become particularly important. Here, we assembled graph-based mitochondrial genomes (mitogenomes) of four Saccharinae species (T. arundinaceum, E. rockii, M. sinensis, and N. porphyrocoma). Then, we performed a comparative mitogenomes analysis of Saccharinae species, including characterization, organelles transfer sequence, collinear sequence, phylogenetics analysis, and gene duplicated/loss. Our results provided the mitogenomes of four species closely related to sugarcane breeding, enriching the mitochondrial genomic resources of the Saccharinae. Additionally, our study offered new insights into the evolution of mitogenomes at the family and genus levels and enhanced our understanding of organelle evolution in the highly polyploid Saccharum genus.